134 A qualitative study of patient perceptions of immunoglobulin treatment regimens for inflammatory neuropathy. Issue 6 (27th May 2022) - Callanan, E; Levee, V; Compton, L; Ramdharry, G; Lunn, M; Carr, A
Abstract : Introduction: With RCT evidence of equivalency between intravenous (IVIg) and subcutaneous (SCIg) immunoglobulin in the management of CIDP, we sought to optimise uptake of homecare SCIg in our inflammatory neuropathy cohort. This is of particular importance in the context of the COVID pandemic. Aim: To explore patient perception of IVIg and SCIg and understand treatment preferences. Methods: We performed a non-hypothesis driven qualitative study of patient perception. Data was collected from adult patients with CIDP via an open-ended telephone interview and a focus group facilitated by medics independent members of the treating team. The data was coded using Braun and Clarke's reflexive thematic analysis. Results: 11 patients were interviewed (mean age=51.55; S.D. 8.70, mean time on immunoglobulin treatment 61 months, S.D. 35.64). Patients found the treatment effective but highlighted perceived side-effects. The hospital environment (IVIg treatment) was reassuring but brought with it a range of difficulties, both logisti- cal and financial. Knowledge and direct experience of SCIg was lacking. Conclusion: We will develop a structured questionnaire based on these themes for broader application across the cohort. From this qualitative data we will continue to adapt our service in a patient focused manner and identify measures of quality improvement. emma: callanan1@nhs.net 92